E-tests as motivational opportunities in mathematics classes - Papp Gabriella; Пап Габріелла (University of Debrecen, 2023)
Abstract. We can read in many studies what techniques are used in the educational process to deepen knowledge and what can motivate students to learn. In the spring semester of the 2021/2022 school year, we carried out action research within the framework of a course, where we examined how much it motivates students if they write an e-test as a retrospective in order to deepen the material of the lesson. The selected course was 20 hours. During the research, the students wrote one input, 6 motivational, and one output e-tests. At the conference, we will present the results of the action research and the experiences we have gained, as well as the students’ opinions regarding the motivating effect of the tests.

Számos tanulmányban olvashatunk arról, hogy az oktatási folyamatban milyen technikákat alkalmaznak a tudás mélyítése érdekében, mik motiválhatják a hallgatókat a tanulásban A 2021/2022-es tanév tavaszi félévében akciókutatást végeztünk egy kurzus keretin belül, ahol azt vizsgáltuk, mennyire motiválja a hallgatókat, ha az óra anyagának elmélyítése céljából, visszatekintésként e-tesztet írnak. A kiválasztott tárgy 20 órás volt. A kutatás során a hallgatók egy bemeneti, 6 motivációs és egy kimeneti e-tesztet írtak. A konferencián bemutatjuk az akciókutatás eredményeit és az általunk szerzett tapasztalatokat, valamint a hallgatók véleményét a tesztek motiváló hatásával kapcsolatban.
E-tesztek, mint motivációs lehetőségek a matematika órákon
https://ojs.lib.unideb.hu/tmcs/article/view/12945
Keywords: e-tests; motivation; mathematics; e-tesztek; motiváció; matematika